Anti-mite tourmaline blend fiber and preparation method thereof
By using the modified Temaline particles in the Tomarin sticky glue fiber, the problem of decreased in the interface binding stability in the temperature of the temperature in the temperature of the temperature of the temperature is used, which has significantly improved the structure Stability and service life.
Patent Information
- Application Number
- CN202411498944.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The interface binding stability of Tomalin particles in viscose fibers is reduced in the temperature sudden change environment, resulting in poor structural stability and service life of Tomalin blended fibers.
By combining zinc oxide through sputtering deposits on Tema Lin's slices, prepare a modified Temain particles, and use the modified particle material in Tema Lin sticky glue fiber Stability in the change environment.
It significantly improves the structural stability of Tema Lin's sticky fiber in the sudden changes in temperature, thereby extending the life of the use of mites to prevent mites.
Smart Images

Figure BDA0005102035360000091 
Figure BDA0005102035360000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of functional fiber materials, and more specifically, to an anti-mite tourmaline blended fiber and a preparation method thereof. Background Art
[0002] Anti-mite tourmaline blended fiber is composed of viscose fiber containing tourmaline particles and anti-mite fiber. It retains the unique properties of tourmaline and has anti-mite function. It can not only release negative ions and emit far infrared rays, improve microcirculation, promote metabolism, activate cells, etc., but also effectively prevent the spread and cross infection of various bacteria, and has antibacterial, antibacterial and anti-mite effects. It has received important attention in textiles and is widely used in bedding, home decoration fabrics, medical and sanitary products and other fields.
[0003] In the preparation of viscose fiber containing tourmaline particles, the cellulose raw material is first extracted, and then treated with caustic soda and carbon disulfide to obtain sodium xanthate of cellulose, which is then dissolved in a dilute sodium hydroxide solution to form a viscous spinning solution, and finally the tourmaline particles are added for wet spinning. For example, the invention patent with patent application number CN201110004886.3 discloses a preparation method of tourmaline viscose fiber, which includes: the tourmaline coarse grinding raw material is wet ultrafine grinding-air flow crushing-preparation of tourmaline slurry, which is characterized in that: when preparing the tourmaline slurry, by selecting appropriate dispersants, abrasives and proportions, and suitable process conditions, the tourmaline particles are further ground while pulping, and finally more than 90% of the tourmaline particles are uniformly and stably sized at 0.3μm, and then the prepared tourmaline slurry is injected before the viscose fiber is wet-spun, and finally the tourmaline viscose fiber with high negative ion release function is obtained.
[0004] Regarding the above-mentioned related technologies, the inventors believe that in the application environment of some specific regions, when the tourmaline particles are affected by sudden temperature changes, their interface bonding stability on the viscose fiber will be reduced, and the tourmaline particles are prone to rupture when affected by sudden temperature changes. At this time, the anti-mite tourmaline blended fiber will be affected by the above-mentioned influence, and the structural stability will be significantly lost, resulting in poor service life performance.
[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0006] In order to improve the application stability of anti-mite tourmaline blended fiber in an environment with sudden temperature changes, the present application provides an anti-mite tourmaline blended fiber and a preparation method thereof.
[0007] In the first aspect, the present application provides an anti-mite tourmaline blended fiber, which adopts the following technical solution: An anti-mite tourmaline blended fiber is obtained by blending tourmaline viscose fiber and anti-mite fiber, wherein the tourmaline viscose fiber is obtained by wet spinning raw materials containing the following parts by weight: 10-12 parts of viscose spinning stock solution; 0.8-1.2 parts of modified tourmaline particles; Dispersant 0.1-0.12 parts; The modified tourmaline particle material is prepared by the following steps: S1, taking a tourmaline sheet, cleaning its surface with alcohol and acetone respectively, then rinsing with deionized water and drying to obtain a pretreated tourmaline sheet; S2, combining zinc oxide on the tourmaline sheet by sputtering deposition, and then crushing and sieving to obtain modified tourmaline particles; In the above sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 75-85 mm, the sputtering power is 40-60 W, the sputtering gas pressure is 0.8-1.5 Pa, the sputtering time is 35-45 min, and the sputtering temperature is 380-420°C.
[0008] By adopting the above technical scheme, in the preparation of modified tourmaline particles, zinc oxide is combined with the tourmaline sheet by sputtering deposition, so that the surface of the modified tourmaline particles can be stably present, and then, in the case of rapid changes in high and low temperatures, the good temperature resistance brought by zinc oxide is utilized, so that the modified tourmaline particles can remain stable in an environment with drastic temperature changes. At the same time, in the process of deposition sputtering, the deposition sputtering conditions are selected as "sputtering gas is Ar, sputtering target substrate distance is 75-85mm, sputtering power is 40-60W, sputtering gas pressure is 0.8-1.5Pa, sputtering time is 35-45min, sputtering temperature is 380-420℃", which can make zinc oxide grains form a large number of holes in the process of deposition, and the grain size is significantly increased, further forming an uneven surface structure, so that the modified tourmaline particles can show strong interface bonding strength in the tourmaline viscose fiber, and are not easily damaged by sudden changes in the external environment temperature. In summary, by using specially modified tourmaline particles in tourmaline viscose fibers, the structural stability of tourmaline viscose fibers in sudden temperature changes can be significantly improved, thereby extending the service life of anti-mite tourmaline blended fibers.
[0009] Preferably, in the above-mentioned sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 80 mm, the sputtering power is 20 W, the sputtering gas pressure is 1 Pa, the sputtering time is 40 min, and the sputtering temperature is 400° C.
[0010] By adopting the above technical scheme and selecting the above deposition parameters, not only can the zinc oxide on the surface of the modified tourmaline particle material be stably combined, but also the zinc oxide structure formed by the deposition can have relatively uniform pores and the unevenness of its surface structure can also be relatively uniform, thereby being able to exert a better corresponding effect in the application and combination process of the modified tourmaline particle material, so that the structural stability of the tourmaline viscose fiber in sudden temperature changes is relatively excellent, and the final anti-mite tourmaline blended fiber is less susceptible to damage and has a better overall service life.
[0011] Preferably, the raw material of the tourmaline viscose fiber also includes 0.1-0.3 parts by weight of a functional additive, the functional additive is composed of titanium dioxide nanotubes and rare earth powder, and the weight ratio of titanium dioxide nanotubes to rare earth powder is (10-15):1.
[0012] By adopting the above technical scheme, titanium dioxide nanotubes have good chemical stability and thermal stability, and can form a network structure in the mixed system of tourmaline viscose fiber, thereby significantly reducing the structural damage caused by sudden changes in external temperature; in addition to enhancing the temperature change resistance of tourmaline viscose fiber, rare earth powder can also modify the surface of modified tourmaline particles, thereby improving the interface bonding stability of modified tourmaline particles; and when titanium dioxide nanotubes and rare earth powder are mixed as functional additives, the two can have an excellent compounding and synergistic effect on each other, and through the holes and uneven structure on the surface of the modified tourmaline particles, an interactive, connected and supporting protective structure can be formed, thereby significantly improving the application stability of anti-mite tourmaline blended fibers in a sudden temperature change environment.
[0013] Preferably, the weight ratio of the titanium dioxide nanotubes to the rare earth powder is 12:1.
[0014] By adopting the above technical scheme, when the titanium dioxide nanotubes and rare earth powders in the above weight ratio are used to form functional additives, the coordinated effect between the two is relatively excellent, and a relatively stable protective structure can be formed with the modified tourmaline particle material, thereby making the tourmaline viscose fiber more stable when used in sudden temperature changes, and finally the service life of the anti-mite tourmaline blended fiber is also better.
[0015] Preferably, the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of (1.4-1.8):1.
[0016] By adopting the above technical scheme, cerium powder and gadolinium powder interact with each other, and the combination of the two can bring better modification effect on the modified tourmaline particle material, improve the interface bonding stability, and improve the temperature change resistance of tourmaline viscose fiber. The overall performance is relatively excellent, and the application of functional additives can better improve the stability of anti-mite tourmaline blended fibers in a sudden temperature change environment.
[0017] Preferably, the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of 1.6:1.
[0018] By adopting the above technical solution, when the rare earth powder composed of cerium powder and gadolinium powder in the above proportion is used, the corresponding effect is better, and the anti-mite tourmaline blended fiber finally obtained has better stability performance in a sudden temperature change environment.
[0019] Preferably, the particle size of the modified tourmaline particles is 0.3-0.5 μm.
[0020] By adopting the above technical scheme, when the particle size of the modified tourmaline particle material is lower than the above range, it is easy to agglomerate during the application process, resulting in the corresponding effect of the zinc oxide deposited on its surface being greatly reduced; when the particle size of the modified tourmaline particle material is higher than the above range, it is not only difficult to distribute evenly, but the zinc oxide deposited on its surface will also find it difficult to overcome the adverse effects of sudden temperature changes; therefore, when the particle size of the modified tourmaline particle material is 0.3-0.5μm, when it is used in tourmaline viscose fiber, it can bring better temperature change resistance improvement, and its own structure is not easily damaged, thereby ensuring the application stability of the anti-mite tourmaline blended fiber in a sudden temperature change environment.
[0021] Preferably, the cellulose content in the viscose spinning stock solution is 5-8%.
[0022] By adopting the above technical scheme, the cellulose content in the viscose spinning stock solution will not only affect the structural strength of the tourmaline viscose fiber, but also affect the interface bonding strength between it and the modified tourmaline particle material. When the cellulose content is selected to be 5-8%, the obtained tourmaline viscose fiber can maintain better structural stability in an environment of sudden temperature changes.
[0023] Preferably, the dispersant is one or a combination of several of sodium polyacrylate, sodium lignin sulfonate, sodium lauryl sulfate, sodium tripolyphosphate and sodium hexametaphosphate.
[0024] By adopting the above technical scheme, the above types of dispersants are all suitable for the preparation of tourmaline viscose fibers, so that the modified tourmaline particles can be evenly dispersed to avoid precipitation or aggregation in the raw material mixing system, thereby obtaining tourmaline viscose fibers with better quality.
[0025] In a second aspect, the present application provides a method for preparing anti-mite tourmaline blended fiber, using the following technical solution: A method for preparing anti-mite tourmaline blended fiber comprises the following steps: (1) preparing raw materials including viscose spinning stock solution, modified tourmaline particle material and dispersant according to a ratio; (2) mixing the viscose spinning stock solution, modified tourmaline particles and a dispersant in step (1) to obtain a spinning mixture, and spinning the mixture through a wet spinning machine to obtain tourmaline viscose fibers; (3) The tourmaline viscose fiber is blended with the anti-mite fiber to prepare the anti-mite tourmaline blended fiber.
[0026] By adopting the above technical scheme, the above preparation method is simple to operate. By directly using the modified tourmaline particle material, tourmaline viscose fiber with excellent temperature-resistant deformation resistance can be obtained, and finally anti-mite tourmaline blended fiber that is stable in the environment of sudden temperature changes can be obtained, which is suitable for large-scale industrial production as a whole.
[0027] In summary, this application has the following beneficial effects: 1. The present application prepares a modified tourmaline particle material and applies it to the preparation of tourmaline viscose fiber. The modified tourmaline particle material exhibits strong interface bonding strength in the tourmaline viscose fiber and structural stability in an environment with drastic temperature changes, so that the tourmaline viscose fiber exhibits excellent structural stability in the application of a temperature sudden change environment, and finally obtains a mite-proof tourmaline blended fiber that is stable in the application of a temperature sudden change environment; 2. The present application uses functional additives composed of titanium dioxide nanotubes and rare earth powder, utilizes the mutual cooperation between the two, and acts on the holes and uneven structures on the surface of modified tourmaline particles, thereby forming an interactive, connected and supported protective structure, so as to significantly improve the application stability of anti-mite tourmaline blended fibers in an environment with sudden temperature changes. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0029] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are commercially available: The anti-mite fiber was purchased from Shaoxing Xineng Textile Technology Co., Ltd., with specifications of 1.5D*38mm; Viscose spinning solution was purchased from Shandong Yinying Chemical Fiber Co., Ltd.; Tourmaline sheets were purchased from Lingshou County Baixin New Material Technology Co., Ltd. with a thickness of 0.5 mm; Titanium dioxide nanotubes were purchased from Guangzhou Hongwu Materials Technology Co., Ltd. with an inner diameter of 5 nm and a length of 1.5 μm; Cerium powder and gadolinium powder were purchased from Beijing Zhongjinyan New Materials Technology Co., Ltd. with a particle size of 5 μm; Sodium polyacrylate was purchased from Anhui Water Guard Environmental Protection Technology Co., Ltd., model SWS-A02.
[0030] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified tourmaline particle material is prepared by the following steps: S1, taking a tourmaline sheet, cleaning its surface with 95% alcohol and acetone respectively, then rinsing with deionized water and drying to obtain a pretreated tourmaline sheet; S2, combining zinc oxide on the tourmaline sheet by sputtering deposition, and then crushing and sieving to obtain modified tourmaline particles; In the above sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 80 mm, the sputtering power is 20 W, the sputtering gas pressure is 1 Pa, the sputtering time is 40 min, and the sputtering temperature is 400° C. The particle size of the modified tourmaline particle material is 0.4 μm.
[0031] Preparation Example 2 A modified tourmaline particle material is different from Preparation Example 1 in that, in the above-mentioned sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 75 mm, the sputtering power is 40 W, the sputtering gas pressure is 0.8 Pa, the sputtering time is 35 min, and the sputtering temperature is 380°C.
[0032] Preparation Example 3 A modified tourmaline particle material is different from Preparation Example 1 in that, in the above-mentioned sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 85 mm, the sputtering power is 60 W, the sputtering gas pressure is 1.5 Pa, the sputtering time is 45 min, and the sputtering temperature is 420°C.
[0033] Preparation Example 4 A modified tourmaline particle material, which is different from Preparation Example 1 in that the particle size of the modified tourmaline particle material is 0.3 μm.
[0034] Preparation Example 5 A modified tourmaline particle material, which is different from Preparation Example 1 in that the particle size of the modified tourmaline particle material is 0.5 μm.
[0035] Preparation Example 6 A modified tourmaline particle material, which is different from Preparation Example 1 in that the particle size of the modified tourmaline particle material is 0.25 μm.
[0036] Preparation Example 7 A modified tourmaline particle material, which is different from Preparation Example 1 in that the particle size of the modified tourmaline particle material is 0.55 μm. Example
[0037] Example 1 An anti-mite tourmaline blended fiber, the weight of the raw materials used in the preparation of which is shown in Table 1, is prepared by the following steps: (1) preparing raw materials including viscose spinning stock solution, modified tourmaline particle material and dispersant according to a ratio; (2) mixing the viscose spinning stock solution, modified tourmaline particles and a dispersant in step (1) to obtain a spinning mixture, and spinning the mixture through a wet spinning machine at a spinning speed of 80 m / min to obtain tourmaline viscose fibers with a specification of 1.5D×38 mm; (3) The tourmaline viscose fiber is blended with the anti-mite fiber to prepare the anti-mite tourmaline blended fiber.
[0038] Note: The modified tourmaline particles are obtained from Preparation Example 1; the cellulose content in the viscose spinning stock solution is 6.5%; the dispersant is sodium polyacrylate; the blending ratio of tourmaline viscose fiber and anti-mite fiber is 65:35.
[0039] Example 2-3 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the weights of the raw materials used in its preparation are shown in Table 1.
[0040] Table 1 Raw materials used in the preparation of Examples 1-3 and their corresponding weights (kg / portion) raw material Example 1 Example 2 Example 3 Viscose spinning solution 11 10 12 Modified Tourmaline Granules 1.0 0.8 1.2 Dispersants 0.11 0.1 0.12 Example 4 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 2.
[0041] Example 5 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 3.
[0042] Example 6 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 4.
[0043] Example 7 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 5.
[0044] Example 8 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 6.
[0045] Example 9 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the modified tourmaline particle material is obtained from Preparation Example 7.
[0046] Example 10 An anti-mite tourmaline blended fiber is different from Example 1 in that the cellulose content in the viscose spinning stock solution is 5%.
[0047] Embodiment 11 An anti-mite tourmaline blended fiber is different from Example 1 in that the cellulose content in the viscose spinning stock solution is 8%.
[0048] Example 12 An anti-mite tourmaline blended fiber is different from Example 1 in that the cellulose content in the viscose spinning stock solution is 4.5%.
[0049] Example 13 An anti-mite tourmaline blended fiber is different from Example 1 in that the cellulose content in the viscose spinning stock solution is 8.5%.
[0050] Embodiment 14 An anti-mite tourmaline blended fiber, which is different from Example 1 in that the raw material of the tourmaline viscose fiber also includes 0.2 parts by weight of a functional additive, the functional additive is composed of titanium dioxide nanotubes and rare earth powder in a weight ratio of 12:1, and the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of 1.6:1; and the functional additive is added together with the modified tourmaline particle material when used.
[0051] Embodiment 15 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the weight portion of the functional additive added is 0.1 part.
[0052] Example 16 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the weight portion of the functional additive added is 0.3 parts.
[0053] Embodiment 17 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the functional additive is composed of titanium dioxide nanotubes and rare earth powder in a weight ratio of 12.5:1.
[0054] Embodiment 18 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the functional additive is composed of titanium dioxide nanotubes and rare earth powder in a weight ratio of 10:1.
[0055] Embodiment 19 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the functional additive is composed of titanium dioxide nanotubes and rare earth powder in a weight ratio of 15:1.
[0056] Embodiment 20 An anti-mite tourmaline blended fiber, which is different from Example 14 in that titanium dioxide nanotubes are not used in the functional additive.
[0057] Embodiment 21 An anti-mite tourmaline blended fiber, which is different from Example 14 in that no rare earth powder is used in the functional additive.
[0058] Embodiment 22 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of 1.4:1.
[0059] Embodiment 23 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of 1.8:1.
[0060] Embodiment 24 An anti-mite tourmaline blended fiber, which is different from Example 14 in that cerium powder is not used in the rare earth powder.
[0061] Embodiment 25 An anti-mite tourmaline blended fiber, which is different from Example 14 in that gadolinium powder is not used in the rare earth powder.
[0062] Comparative Example Comparative Example 1 An anti-mite tourmaline blended fiber is different from Example 1 in that the modified tourmaline particle material is replaced by the unmodified tourmaline particle material.
[0063] Comparative Example 2 An anti-mite tourmaline blended fiber, which is different from Example 14 in that the modified tourmaline particle material is replaced by the unmodified tourmaline particle material.
[0064] Performance testing test samples: The anti-mite tourmaline blended fiber obtained in Example 1-25 was used as test sample 1-25, and the anti-mite tourmaline blended fiber obtained in Comparative Example 1-2 was used as control sample 1-2.
[0065] Test method: (1) Use a universal tensile testing machine to fix the anti-mite tourmaline blended fiber on the testing machine, clamp and mark it according to the requirements of the testing machine, pull the clamps apart by a certain distance so that the sample begins to be stretched and deformed, and record the tensile force value displayed by the testing machine while continuously increasing the distance between the clamps. When the sample is broken, the maximum tensile force displayed by the testing machine is the breaking strength value of the anti-mite tourmaline blended fiber, which is recorded as the initial value G1; (2) The anti-mite tourmaline blended fiber is placed in a temperature alternating test chamber, with the initial experimental temperature being 25°C. The temperature is first raised to 80°C at a rate of 4°C / min, maintained for 30 minutes, then lowered to -10°C at a rate of 2°C / min, maintained for 10 minutes, and then raised to 25°C at a rate of 1.5°C / min, maintained for 5 minutes, which is recorded as one cycle. After 10 cycles, the test is performed again according to the same method as in (1) above, and the breaking strength value obtained at this time is recorded as G2. (3) Finally, the breaking strength loss rate is calculated, which is (G1-G2) / G1. The greater the breaking strength loss rate, the worse the application stability of the anti-mite tourmaline blended fiber in a temperature sudden change environment.
[0066] After completing the above tests on test samples 1-25 and control samples 1-2 in sequence, the test results are recorded in the following Table 2.
[0067] Table 2 Test results of test samples 1-25 and control samples 1-2 It can be seen from Examples 1-3 and Comparative Example 1 and Table 2 that the present application prepares modified tourmaline particles and applies them to the preparation of tourmaline viscose fibers, so that the final anti-mite tourmaline blended fibers can exhibit excellent temperature change resistance, maintain relatively excellent structural stability in applications in sudden temperature change environments, and the breaking strength loss rate obtained by the above test is also significantly reduced.
[0068] It can be seen from Example 1 and Example 4-5 and Table 2 that in the sputtering deposition process for the preparation of the modified tourmaline particles, the sputtering gas is Ar, the sputtering target-base distance is 75-85 mm, the sputtering power is 40-60 W, the sputtering gas pressure is 0.8-1.5 Pa, the sputtering time is 35-45 min, and the sputtering temperature is 380-420 ° C., which can ensure that the obtained modified tourmaline particles not only show strong interface bonding strength after application, but also are not easily damaged by sudden changes in external environmental temperature, thereby ensuring the structural stability of the final anti-mite tourmaline blended fiber in sudden temperature changes.
[0069] It can be seen from Example 1 and Examples 6-9 and Table 2 that the particle size of the modified tourmaline particles is 0.3-0.5 μm, which can ensure that the modified tourmaline particles can bring better temperature change resistance when used in tourmaline viscose fibers; and when the particle size is lower than the above range, it will lead to an increase in the breaking strength loss rate of the anti-mite tourmaline blended fiber obtained by the above test, indicating that the modified tourmaline particles in the above particle size range can ensure that it exerts its excellent and stable characteristics, thereby ensuring the application stability of the anti-mite tourmaline blended fiber in an environment with sudden temperature changes.
[0070] It can be seen from Example 1 and Examples 10-13 and Table 2 that when the cellulose content in the viscose spinning stock solution is 5-8%, the viscose spinning stock solution and the modified tourmaline particle material can maintain excellent and stable interface bonding strength, while when it exceeds the above range, it will lead to a decrease in the interface bonding stability, so that the final anti-mite tourmaline blended fiber will show an increased loss rate of breaking strength after the above test.
[0071] Combining Example 1 and Example 14-19 with Table 2, it can be seen that by using a functional additive composed of titanium dioxide nanotubes and rare earth powder, the loss rate of breaking strength can be significantly reduced, indicating that the application stability of the anti-mite tourmaline blended fiber in a temperature sudden change environment is significantly improved; when the weight ratio of titanium dioxide nanotubes and rare earth powder is 12:1, the corresponding improved quality of the anti-mite tourmaline blended fiber is better. Combining Example 20-21 with Table 2, it can be seen that if any one of titanium dioxide nanotubes and rare earth powder is used as a functional additive, it can bring about an improvement in temperature change resistance, but the improvement effect is limited, and the sum of the improvement effects brought by the use of each of the two alone is far less than the excellent improvement effect brought by the combination of the two, indicating that the combination of titanium dioxide nanotubes and rare earth powder can bring a significant improvement effect of 1+1>2. Combined with Examples 22-25 and Table 2, it can be seen that when the rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of (1.4-1.8): 1, the functional additive can be guaranteed to bring a better application improvement effect, and any one of the cerium powder and gadolinium powder is used alone as a rare earth powder, the application effect of the functional additive will be greatly discounted. It can be seen that the combination of cerium powder and gadolinium powder is more suitable for the application of functional additives. Combined with Comparative Examples 1-2 and Table 2, it can be seen that when the functional additive plays an excellent role, it needs to be matched with modified tourmaline particles. If the modified tourmaline particles are replaced with unmodified tourmaline particles, it is found that the corresponding effect brought by the functional additive will be significantly discounted. It can be seen that there is a compounding effect between the functional additive and the modified tourmaline particles, which can significantly improve the application stability of the anti-mite tourmaline blended fiber in a temperature sudden change environment.
[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An anti-mite tourmaline blended fiber, characterized in that: The tourmaline viscose fiber is blended with anti-mite fiber, and the tourmaline viscose fiber is prepared by wet spinning of raw materials containing the following parts by weight: 10-12 parts of viscose spinning stock solution; 0.8-1.2 parts of modified tourmaline particles; Dispersant 0.1-0.12 parts; The modified tourmaline particle material is prepared by the following steps: S1, taking a tourmaline sheet, cleaning its surface with alcohol and acetone respectively, then rinsing with deionized water and drying to obtain a pretreated tourmaline sheet; S2, combining zinc oxide on the tourmaline sheet by sputtering deposition, and then crushing and sieving to obtain modified tourmaline particles; In the above sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 75-85 mm, the sputtering power is 40-60 W, the sputtering gas pressure is 0.8-1.5 Pa, the sputtering time is 35-45 min, and the sputtering temperature is 380-420°C.
2. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: In the above sputtering deposition process, the sputtering gas is Ar, the sputtering target substrate distance is 80 mm, the sputtering power is 20 W, the sputtering gas pressure is 1 Pa, the sputtering time is 40 min, and the sputtering temperature is 400°C.
3. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: The raw material of the tourmaline viscose fiber also includes 0.1-0.3 parts by weight of a functional additive, which is composed of titanium dioxide nanotubes and rare earth powder, and the weight ratio of the titanium dioxide nanotubes to the rare earth powder is (10-15):
1.
4. The anti-mite tourmaline blended fiber according to claim 3, characterized in that: The weight ratio of the titanium dioxide nanotubes to the rare earth powder is 12:
1.
5. The anti-mite tourmaline blended fiber according to claim 3, characterized in that: The rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of (1.4-1.8):
1.
6. The anti-mite tourmaline blended fiber according to claim 5, characterized in that: The rare earth powder is composed of cerium powder and gadolinium powder in a weight ratio of 1.6:
1.
7. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: The particle size of the modified tourmaline particles is 0.3-0.5 μm.
8. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: The cellulose content in the viscose spinning stock solution is 5-8%.
9. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: The dispersant is one or a combination of sodium polyacrylate, sodium lignin sulfonate, sodium lauryl sulfate, sodium tripolyphosphate and sodium hexametaphosphate.
10. The anti-mite tourmaline blended fiber according to claim 1, characterized in that: The following steps are involved: (1) preparing raw materials including viscose spinning solution, modified tourmaline particles and dispersant according to the ratio; (2) mixing the viscose spinning stock solution, modified tourmaline particles and a dispersant in step (1) to obtain a spinning mixture, and spinning the mixture through a wet spinning machine to obtain tourmaline viscose fibers; (3) The tourmaline viscose fiber is blended with the anti-mite fiber to produce the anti-mite tourmaline blended fiber.
Citation Information
Patent Citations
Preparation method of tourmaline viscose fibers
CN102121139A
Anti-acarid modal fibre fabric
CN103526423A
Antibacterial and mildewproof waterborne polyurethane coating
CN108441098A
Anti-mite blended fabric
CN109706574A
Modification method of fibers for preparing carbon fiber paper and application of fibers
CN111876995A